Valence Bond‐Based Hybrid Quantum Mechanics Molecular Mechanics Approaches and Proper Inclusion of the Effect of the Surroundings. Issue 8 (16th July 2014) - Shurki, Avital; Sharir‐Ivry, Avital
Abstract The pioneering development of multiscale models for complex chemical systems by Karplus, Levitt, and Warshel, including the hybrid quantum mechanics molecular mechanics (QM/MM) approach and its application to enzymes, established a new field in chemistry that allows the modeling of reactivity within complex chemical systems. Inspired by the potential of such methods, many groups developed different QM/MM variants. Valence bond (VB) theory, which always was and still is an important conceptual tool for chemists, is well suited to deal with problems of chemical reactivity. Hence, here we review VB‐based QM/MM methods, including the early semi‐empirical methods that utilize VB concepts and more recent ab initio VB‐based QM/MM methods. Special emphasis is given to the different ways to include effects of the surroundings on the solute. It is shown that within the VB framework, simple mechanical embedding for each diabatic state, followed by mixing of the states, accounts for most of these effects.